KLASYFIKACJA ŚRODKÓW PRAWNYCH PRZECIWDZIAŁANIA BEZROBOCIU – WYBRANE ZAGADNIENIA - Staszewska, Ewa (Zeszyty Prawnicze, 2016)
CLASSIFICATION OF LEGAL MEASURES TO COUNTERACT UNEMPLOYMENT: SELECTED ASPECTS Summary In order to effectively counteract unemployment the state needs to adopt and pursue an appropriate policy. The law is obviously one of the instruments which the state can use to curb unemployment. In particular, labour law regulations serve as an institutional and legal framework used by the state to achieve its goals within the area of fighting unemployment. The present article focuses on the classification of legal measures of counteracting unemployment as defined by the Polish Act of 20th April 2004 on the Promotion of Employment and Labour Market Institutions. The author defines two areas of fighting unemployment. The first area comprises measures taken by the state to assist the unemployed in finding new jobs and help them to adapt to the requirements of the labour market. The second area includes the state’s actions to create new jobs and the occupational activation of the unemployed. The author emphasises the fact that certain measures for counteracting unemployment are addressed specifically to groups whose social and demographic status puts them at greater risk of unemployment.